Soil-transmitted helminth infection and skin prick test reactivity in children - Schenny Regina Lubis; Lily lrsa; Rita Evalina; Supriatmo Supriatmo; M. Sjabaroeddin (Indonesian Pediatric Society, 2014)
Background Allergic diseases cause an increasingly largeburden in developed countries and in urban areas of middleincomecountries . Paras itic infections may induce allergicresponses in humans, particularly soil-transmitted helminth(STH) infections that are prevalent in childhood in developingcountries. Although soil-transmitted helminth infec tions havebeen associated with lower prevalence of allergen skin testreactivity, study outcomes remain inconclusive.Objective To analyze for an association between STH infectionsand skin prick test reactivity in children.Methods We conducted a cross-sectional study in August 2009among primary school students aged 7- 12 years, at SecanggangSubdistrict, Langkat District, North Sumatera Province. Sixtyeight children were recruited in this study consisted of 34 childrenwith STH infections and the other 34 children without any STHinfection. Soil-transmitted helminth infections were determinedby Kato-Katz stool examination s. All subjects underwent skinprick tests for seven allergens. Results were con sidered to bepositive if wheal diameters 2: 3 mm and negative when whealdiameters < 3 mm. Data was an alysed by Chi-square test.Results Stool examinations revealed that the most commoninfec tion was T. trichiura (18/34 subjects), followed by mixedinfections (T. trichiura and A lumbricoides; 12/34 subjects), andA. lumbricoides (4134 subjects). There was a significant associationbetween STH infections and negative skin prick test (P= 0.002).In addition, there were significant associations with negative skinprick tests for each helminth type: A. lumbricoides (P=0.001) ,T. trichiura (P=0.01) and mixed infection (P = 0.006). Severeinfection intensity was also significantly associated with negativeskin prick tests (P=0.031) .Conclusion Children with STH infections tend to have negativeskin prick test results.